Burning bodies : community, eschatology, and the punishment of heresy in the Middle Ages - Barbezat, Michael D. (Ithaca [New York] : Cornell University Press, 2018)
"Interrogates the ideas that the authors of historical and theological texts in the medieval West associated with the burning alive of Christian heretics, tracing them from the earliest instances in the eleventh century until the advent of the internal crusades of the thirteenth century"--
Introduction : burning bodies and medieval human communal identity -- Our God is like a consuming fire : burning bodies and Christian community -- Fields and bodies : toleration and threat in a shared space -- The beginning at Orleans in 1022 : heretics and hellfire -- Likeness in difference : three burnings in the twelfth-century Rhineland -- Like rejoices in like : recognition and differentiation in descriptions of heresy -- Heresy, sex, and reading in the late twelfth and early thirteenth centuries -- Leaping from the flames : love, redemption, and holy war in the Albigensian Crusade -- Conclusion : the uses of exclusion and fear for a community of love.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
OCLC control number change
Keywords: Human body -- Religious aspects -- Christianity -- History of doctrines -- Middle Ages, 600-1500.; Flesh (Theology) -- History of doctrines -- Middle Ages, 600-1500.; Fire -- Religious aspects -- Christianity; Christian heretics -- Europe -- History; Europe -- Church history -- 600-1500.; Christian heretics; Fire -- Religious aspects -- Christianity; Europe; RELIGION / History; 600-1500; Church history; History; Electronic books